Using power series method,solve the following differential equation
(x3+3)y"+4xy'+y=0
Let "y = \\sum_{n=0}^{\\infty}a_nx^n"
Then "y' = \\sum_{n=1}^{\\infty}na_nx^{n-1}"
And "y'' = \\sum_{n=2}^{\\infty}n(n-1)a_nx^{n-2}"
Then we have that
"(x^3+3)y'' = \\sum_{n=2}^{\\infty}n(n-1)a_nx^{n+1} + \\sum_{n=2}^{\\infty}3n(n-1)a_nx^{n-2} ... (*)"
Also
"4xy' = \\sum_{n=1}^{\\infty}4na_nx^{n} ... (**)"
Adding up and simplifying y, (*) and (**), we have
"\\sum_{n=3}^{\\infty}(n-1)(n-2)a_{n-1}x^{n} + \\sum_{n=0}^{\\infty}3(n+1)(n+2)a_{n+2}x^{n}"
+"a_0 + \\sum_{n=1}^{\\infty}(4n+1)a_nx^n = 0"
Simplifying further, we have
"\\sum_{n=3}^{\\infty} \\big[(n-1)(n-2)a_{n-1} +3(n+1)(n+2)a_{n+2} +(4n+1)a_n \\big]x_n"
"+ 6a_2 + 18a_3x+36a_4x^2+a_0+5a_1x+9a_2x^2 = 0"
Considering
"\\sum_{n=3}^{\\infty} \\big[(n-1)(n-2)a_{n-1} +3(n+1)(n+2)a_{n+2} +(4n+1)a_n \\big]x_n"
when "n \\geq 1," we have that
"a_{n+2} = \\dfrac{(1-n)(n-2)a_{n-1} - (4n+1)a_n}{3(n+1)(n+2)}"
So the solution to the differential equation is
"y = a_0 + a_1x +a_2x^2" "+ \\sum_{n=1}^{\\infty} \\big[ \\dfrac{(1-n)(n-2)a_{n-1} - (4n+1)a_n}{3(n+1)(n+2)} \\big]x^{n+2}"
Comments
Leave a comment